Cultural values in strategy and organization - Das, T. K. 1938- (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"The field of strategy science has grown in both the diversity of issues it addresses and the increasingly interdisciplinary approaches it adopts in understanding the nature and significance of problems that are continuously emerging in the world of human endeavor. These newer kinds of challenges and opportunities arise in all forms of organizations, encompassing private and public enterprises, and with strategies that experiment with breaking the traditional molds and contours. The field of strategy science is also, perhaps inevitably, being impacted by the proliferation of hybrid organizations such as strategic alliances, the upsurge of approaches that go beyond the customary emphasis on competitiveness and profit making, and the intermixing of time-honored categories of activities such as business, industry, commerce, trade, government, the professions, and so on. The blurring of the boundaries between various areas and types of human activities points to a need for academic research to address the consequential developments in strategic issues. Hence, research and thinking about the nature of issues to be tackled by strategy science should also cultivate requisite variety in issues recognized for research inquiry, including the conceptual foundations of strategy and strategy making, and the examination of the critical roles of strategy makers, strategic thinking, time and temporalities, business and other goal choices, diversity in organizing modes for strategy implementation, and the complexities of managing strategy, to name a few. This book series on Research in Strategy Science aims to provide an outlet for ideas and issues that publications in the field do not provide, either expressly or adequately, especially as regards the comprehensive coverage deserved by certain emerging areas of interest. The topics of the volumes in the series will keep in view this objective to expand the research areas and theoretical approaches routinely found in strategy science, the better to permit expanded and expansive treatments of promising issues that may not sufficiently align with the usual research coverage of publications in the field. Cultural Values in Strategy and Organization contains contributions by leading scholars on the role of cultural values in the field of strategy science research. The 11 chapters in this volume cover the topics of ecological organizing and evolving cultural values, corporate cultural responsibility, cultural integration in mergers and acquisitions, culture and paradoxical frames, cultural values in the fair trade market, national culture and legitimacy, family businesses as values-driven organizations, cultural intelligence of executives, building an alliance culture, personal values of civil engineers and architects, and cultural characteristics of Chilean and Brazilian workforces. The chapters collectively present a wide-ranging review of the noteworthy research perspectives on the role of cultural values in strategy and organization"-- Provided by publisher.
Keywords: Social responsibility of business.; Organizational behavior.; Corporate culture.; Business & Economics -- Organizational Behavior.; Organizational theory and behaviour.; elektronické knihy; electronic books